Three-dimensional visualization measurement and analysis of human hepatic pedicle based on Laennec’s capsule - Lin, Zhiyu; Xia, Xin; Luo, Yuchuan; Lei, Huan; Liang, Hongyin; Zhang, Hui; Jiang, Zhiwei; Wang, Tao (Frontiers in Surgery, 2025)
BackgroundLaennec's capsule serves as a crucial anatomical landmark in liver surgery, yet imaging-based morphometric studies of this fibrous membrane remain limited. This study introduces a novel 3D reconstruction technique to visualize and measure the hepatic pedicle via Laennec's capsule, with validation focused on the left portal branch and development of a 3D-printed model for surgical planning.Methods30 patients undergoing left hemihepatectomy were recruited to validate the accuracy of a Laennec's capsule-based 3D reconstruction system (Hisense CAS). Preoperative measurements of the left branch length, diameter, and the angle between the main trunk and the hepatic pedicle were compared with intraoperative findings. Additionally, 100 adults without hilar lesions underwent 3D reconstruction for comprehensive morphological classification and statistical analysis of the hepatic pedicle trunk and main branches.ResultsNo statistically significant differences emerged between the 3D reconstruction data and intraoperative measurements, confirming the method's accuracy. Four distinct branching patterns were identified, with Type I accounting for 88% of cases. At the first hepatic hilum, the mean outer diameter of the hepatic pedicle was 24.10 ± 6.16 mm. The left and right main branches demonstrated considerable variability in length (20.59 ± 6.38 mm vs. 21.99 ± 7.97 mm) and outer diameter (18.04 ± 4.48 mm vs. 21.18 ± 4.23 mm). The angle between the left and right main branches was 140.81 ± 16.72°. Furthermore, a 3D-printed liver model was developed to aid in surgical planning and education.ConclusionsThree-dimensional reconstruction based on Laennec's capsule accurately reflects hepatic pedicle anatomy and its variations. The predominance of Type I branching underscores the need for precise classification during liver surgery. This approach provides valuable morphological data for individualized surgical planning, improves intraoperative safety, and sets the stage for further research integrating alternative imaging modalities and larger patient cohorts.